Stroke Incidence in Victoria, Australia—Emerging Improvements - Clissold, Benjamin B.; Sundararajan, Vijaya; Cameron, Peter; McNeil, John (Frontiers in Neurology, 2017)
BACKGROUND - Evidence of a decline in the incidence of stroke has emerged from population-based studies. These have included retrospective and prospective cohorts. However, in Australia and other countries, government bodies and stroke foundations predict a rise in the prevalence of stroke which is anticipated to increase the burden of stroke across the entire domain of care. This increase in prevalence must be viewed as different from the decline in incidence being observed, a measure of new stroke cases. In Victoria, all public emergency department visits and public and private hospital admissions are reported to the Department of Health and Human Services and include demographic, diagnostic, and procedural/treatment information. METHODS - We obtained data from financial years 1997/8 to 2007/8 inclusive, for all cases with a primary stroke diagnosis (ICD-10-AM categories) with associated data fields. Incident cases were established by using a 5-year clearance period. RESULTS - From 2003/2004 to 2007/2008 inclusive, there were 53425 patients with a primary stroke or TIA diagnosis. The crude incident stroke rate for first ever stroke was 211 per 100000 per year (95% CI 205 – 217) (females - 205 per 100000 per year (95% CI 196 – 214), males - 217 per 100000 per year (95% CI 210 – 224)). The overall stroke rates were seen to significantly decline over the period (males (per 100000 per year) 227 in 2003/2004 to 202 in 2007/2008 (p = 0.0157)), (females (per 100000 per year) 214 in 2003/2004 to 188 in 2007/2008 (p = 0.0482)). Ischaemic stroke rates also appeared to decline, however, this change was not significant. CONCLUSION - These results demonstrate a significant decline in stroke incidence during the study period and may suggest evidence for effectiveness of primary and secondary prevention strategies in cerebrovascular risk factor management.